Rome and provincial resistance - Gambash, Gil 1973- (Routledge Monographs in Classical Studies, 2015)
"This book demonstrates and analyzes patterns in the response of the Imperial Roman state to local resistance, focusing on decisions made within military and administrative organizations during the Principate. Through a thorough investigation of the official Roman approach towards local revolt, author Gil Gambash answers significant questions that, until now, have produced conflicting explanations in the literature: Was Rome's rule of its empire mostly based on oppressive measures, or on the willing cooperation of local populations? To what extent did Roman decisions and actions indicate a dedication towards stability in the provinces? And to what degree were Roman interests pursued at the risk of provoking local resistance? Examining the motivations and judgment of decision-makers within the military and administrative organizations...from the emperor down to the provincial procurator...this book reconstructs the premises for decisions and ensuing actions that promoted negotiation and cooperation with local populations. A ground-breaking work that, for the first time, provides a centralized view of Roman responses to indigenous revolt, Rome and Provincial Resistance is essential reading for scholars of Roman imperial history"...From publisher's website